Microsoft Dynamics AX 2012 R2 Services. - Deforche, Klaas (Professional expertise distilled, 2014)
In Detail Integrating Microsoft Dynamics AX 2012 with other applications will always be necessary within any organisation, and services is the best way of achieving this. With Microsoft Dynamics AX 2012 being more flexible than ever when it comes to creation and use, understanding these services will help you to know when and where to use them for the best result. Starting from ground up, we will build your knowledge of Microsoft Dynamics AX 2012 R2 Services through step by step tutorials, to give you the ability to create and use the most suited service to the task at hand. Starting with service architecture and deployment, we'll quickly take you through to AIF Document services and on to creating custom services for all of your AX needs. This second edition also features information on high availability, load balancing and creating clusters so that you can get the most of your AX services. We then conclude with tracing and debugging, to troubleshoot and monitor running services. Approach Step by step tutorials that guide you through everything you need to know to begin working with Microsoft Dynamics AX services. Who this book is for If you're a Dynamics AX developer, either new to or experienced with services, you'll benefit from this book. A basic understanding of MorphX and X++ is assumed, but the steps are easy to follow even for beginners.